The toll like receptor 7 pathway and the sex bias of systemic lupus erythematosus - Scofield, R. Hal; Wren, Jonathan D.; Lewis, Valerie M. (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) predominately affects women with a ratio of females-to-males of about 9:1. The complement of sex chromosomes may play and important role in the mechanism of the sex bias. Previous work has shown that men with Klinefleter’s syndrome (47,XXY) as well as women with 47,XXX are found in excess among SLE patients well as among Sjogren’s disease, systemic sclerosis and idiopathic inflammatory myositis. in cells with more than one X chromosome, all but one is inactivated. However, X chromosome inactivation, as mediated by the long noncoding RNA X-inactive specific transcript, or XIST, is not complete with approximately 10% of genes in the non-recombining region of the X chromosome escaping X inactivation. In the TLR7 signaling pathway, both the TLR7 and TLR adaptor interacting with endolysosomal SLC15A4 (TASL) escape X inactivation. Comparing male and female immune cells, there is increased TLR7 signaling related to increased expression of these genes in cells with more than one X chromosome. Cells with more than one X chromosome also express XIST, while cells with one X chromosome do not. XIST, as a source of ligand for TLR7, has also been shown to increase TLR7 signaling. Thus, we propose that both these mechanisms operating in immune cells with more than one X chromosome may act in a mutual way to mediate an X chromosome dose effect for the sex bias of autoimmune disease.